A preanodized 6B-pencil graphite as an efficient electrochemical sensor for mono-phenolic preservatives (phenol and meta-cresol) in insulin formulations. Issue 5 (23rd January 2015) - Vishnu, Nandimalla; Kumar, Annamalai Senthil
Abstract : A low-cost pre-anodized 6B-pencil graphite (6B-PGE*) is shown as a fouling-free and renewable electrochemical sensor for mono-phenols and can be used for the detection of mono-phenolic preservatives in pharmaceutical insulin formulations. Abstract : Electrochemical oxidation of phenol on carbon electrodes has often been associated with problems such as serious adsorption, formation of electro-inactive tarry polymers and surface fouling. Thus, it is highly challenging to develop a phenol electrochemical sensor without encountering such problems. Alternately, biosensors, which comprise of enzymes such as tyrosinase and polyphenol oxidase, were widely used for the aforesaid purpose. Herein, we introduce an ultra-low cost 6B grade pencil graphite, pre-anodized at 2 V vs. Ag/AgCl, designated as 6B-PGE*, where * = preanodized, as a novel electrochemical sensor for surface fouling-free and efficient differential voltammetric (DPV) detection of phenols ( meta -cresol and phenol) in pH 7 phosphate buffer solution (PBS). A well-defined cyclic voltammetric peak at 0.65 ± 0.02 V vs. Ag/AgCl, which is stable under multiple electrochemical cycling, was noticed upon electrochemical-oxidation of meta -cresol and phenol at 6B-PGE*. The 6B-PGE* showed eight times higher DPV current signal and 60 mV lower oxidation potential than non-preanodized electrode (PGE) for the phenol detection. Under optimal DPV conditions, the 6B-PGE* showed a linear calibration plot with current linearity in a range of 40–320 μM with current sensitivity and detection limit (signal-to-noise = 3) values of 1.43 μA μM −1 cm −2 and 120 nM, respectively. Six repeated detections of 80 μM meta -cresol without any interim surface cleaning process showed a relative standard deviation (RSD) value of 0.21%. This electro-analytical approach was validated by testing total phenolic contents in three different insulin formulations with an electrode recovery value of ∼100%.